2013
DOI: 10.21608/jappmu.2013.71019
|View full text |Cite
|
Sign up to set email alerts
|

UTILIZATION OF DISTILLERS DRIED GRAINS WITH SOLUBLES IN FISH NUTRITION: 1-REPLACEMENT SOYBEAN MEAL AND YELLOW CORN BY DDGS GRADED LEVELS IN DIET FOR NILE TILAPIA FINGERLINGS ( Oreochromis niloticus).

Abstract: This study was conducted to evaluate the effect of feeding different levels of DDGS in the diets of tilapia fingerlings on growth performance, feed utilization, chemical composition of the whole fish body, blood hematological and economic efficiency. Therefore, five grading levels of DDGS (0, 5, 10, 15 and 20% (D1-D5)) were used to replace soybean meal and yellow corn protein in approximately five isonitrogenous and isocaloric diets. Fish were stocked in a rearing plastic tank for two weeks adaptation period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, Barneset al (2012) suggested that DDGS decreased juvenile rainbow trout growth at dietary concentrations of at 10% or greater. Additionally, Gabret al 2013and Khalil et al (2013) concluded that DDGS could replace 10-16 % of fishmeal (or soybean, respectively) and yellow corn in diets of Nile tilapia fingerlings without any adverse effect on growth performance.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, Barneset al (2012) suggested that DDGS decreased juvenile rainbow trout growth at dietary concentrations of at 10% or greater. Additionally, Gabret al 2013and Khalil et al (2013) concluded that DDGS could replace 10-16 % of fishmeal (or soybean, respectively) and yellow corn in diets of Nile tilapia fingerlings without any adverse effect on growth performance.…”
Section: Growth Performancementioning
confidence: 99%
“…However,Godaet al 2011concluded that replacing up to 60 % of soybean meal by DDGS for 84 days enhanced feed utilization. Gabret al 2013and Khalil et al (2013) concluded that DDGS could replace 10-16 % of FM (or soybean, respectively) and yellow corn in diets of Nile tilapia fingerlings without any adverse effect on feed utilization. Øverlandet al (2013)had evaluated DDGS in diets for rainbow trout.…”
Section: Feed Utilizationmentioning
confidence: 99%